First observation of paired microseismic signals during solution salt mining - Qian, Jiawei; Wang, Kangdong; Zhang, Haijiang; Tan, Yuyang; Xu, Chuanjian; Wang, Qingsong; Xiong, Qiangqing; Malinowski, Michal (Frontiers in Earth Science, 2022)
To monitor the status of cavern roof instability induced by solution salt mining, we deployed a surface microseismic monitoring system for Dongxing salt mine, Dingyuan county, China. The microseismic monitoring system consists of 11 three-component geophones installed in shallow holes of 5 meters deep. From 7-month continuous monitoring data, we have detected a novel type of signal that consists of two events. The first event has a long duration (> 15 s) and generally has higher frequencies at the beginning. The 2nd event has a shorter duration of ~3 seconds with lower frequencies. The two events are separated by ~30-90 s in time. From May 2017 to November 2017, there are a total of 88 distinct paired signals with two events in sequence. We propose the first event corresponds to a series of fracturing processes on the cavern roof, and microseismic signals associated with different fractures are mixed and overlapped to produce a mixed signal with a longer duration. Due to a series of fracturing processes, some zones of cavern roof become instable and some rock debris may fall from the roof and collide on the cavern floor. This collision can produce a short duration signal, which corresponds to the 2nd event of the paired signal. The further analysis of polarities of the first arrivals for the 2nd event further proves its collision origin. The time interval between two events is related to the time for the falling rock debris through the brine, which is controlled by the cavern height and various physical properties of the rock debris and brine. Through the detailed analysis of paired signals, we can have a better understanding of the cavity development status for solution salt mining.